2016
DOI: 10.1063/1.4941078
|View full text |Cite
|
Sign up to set email alerts
|

Strong coupling in molecular exciton-plasmon Au nanorod array systems

Abstract: We demonstrate here strong coupling between localized surface plasmon modes in self-standing nanorods with excitons in a molecular J-aggregate layer though angular tuning. The enhanced exciton−plasmon coupling creates a Fano like line shape in the differential reflection spectra associated with the formation of hybrid states, leading to anti-crossing of the upper and lower polaritons with a Rabi frequency of 125 meV. The recreation of a Fano like line shape was found in photoluminescence demonstrating changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Raman spectroscopy SERS measurements were performed using a bespoke Raman system comprising an inverted optical microscope (IX71, Olympus) with a 50x, 0.42 numerical aperture objective used to focus the 532 nm, 5 mW incident power laser (ThorLabs) to a spot size of ~ 10 μm, 52 a beam splitter and a long pass filter (RazorEdge, Semrock), a spectrograph (SP-2300i, Princeton Instruments), and a CCD camera (IXON, Andor). Raman spectra were collected with an exposure time of 1 s. 60 μl of TMPyP or adenine, at specified concentrations, was deposited on the Fmoc-FF/Ag NP templates.…”
Section: Scanning Electron Microscopy (Sem)mentioning
confidence: 99%
“…Raman spectroscopy SERS measurements were performed using a bespoke Raman system comprising an inverted optical microscope (IX71, Olympus) with a 50x, 0.42 numerical aperture objective used to focus the 532 nm, 5 mW incident power laser (ThorLabs) to a spot size of ~ 10 μm, 52 a beam splitter and a long pass filter (RazorEdge, Semrock), a spectrograph (SP-2300i, Princeton Instruments), and a CCD camera (IXON, Andor). Raman spectra were collected with an exposure time of 1 s. 60 μl of TMPyP or adenine, at specified concentrations, was deposited on the Fmoc-FF/Ag NP templates.…”
Section: Scanning Electron Microscopy (Sem)mentioning
confidence: 99%
“…44 Fedele et al found the recreation of a Fano-like line shape in PL spectra demonstrating changes in the emission spectral profile under strong coupling. 46 Rodriguez et al investigated the emission angular spectra of an Al nanoantenna array embedded in an organic dye slab waveguide and demonstrated the transition from weak to strong coupling between localized surface plasmons (LSPs) in the nanoantennas and the fundamental guided mode in the slab. 47 Eizner et al also studied the emission properties of the hybrid exciton-LSP states in the complexes of Al nanoantennas coated with molecular J-aggregates.…”
mentioning
confidence: 99%
“…Bellessa et al found the upper polariton (UP) state is not present in the luminescence spectra, which is the case in Ag­(I)–carboxylate nanoclusters . Fedele et al found the recreation of a Fano-like line shape in PL spectra demonstrating changes in the emission spectral profile under strong coupling . Rodriguez et al investigated the emission angular spectra of an Al nanoantenna array embedded in an organic dye slab waveguide and demonstrated the transition from weak to strong coupling between localized surface plasmons (LSPs) in the nanoantennas and the fundamental guided mode in the slab .…”
mentioning
confidence: 99%
“…In addition, to providing PIERS-based processes semiconductors can produce metal-semiconductor junctions that enable effective carrier separation through the formation of a Schottky junction [26,[29][30][31]. This junction is formed when the metal and semiconductor are in intimate contact, where the electrons from either semiconductor or metal migrate toward the other component to equilibrate their Fermi levels [23,[32][33][34]. A widely used conducting organic semiconductor is a blend of p and n-type semiconductors e.g.…”
Section: Introductionmentioning
confidence: 99%